Feasibility and Acceptability of a Lifestyle Intervention for Individuals with Bipolar Disorder - Sylvia, Louisa G. (J Psychiatr Pract, 2019)
Individuals with bipolar disorder are at greater risk for cardiovascular disease and are less likely to adhere to lifestyle interventions than the general population. To decrease cardiovascular risk and improve adherence to lifestyle interventions, we developed the Nutrition Exercise and Wellness Treatment (NEW Tx). NEW Tx is an 18 session, 20-week cognitive behavioral therapy (CBT)-based treatment comprising 3 modules: Nutrition, Exercise, and Wellness. To evaluate the feasibility and acceptability of this intervention as well as predictors of treatment satisfaction and expectations, 38 adult outpatients with bipolar disorder were randomized to either NEW Tx or a waitlist control condition. There was no statistically significant difference in drop-out rates between the groups (26.3% in NEW Tx, 31.6% in the control condition). In the NEW Tx condition, participants attended a mean of 66.7% of sessions and reported moderate to high satisfaction. There were no study-related adverse events. We also found that expectations, but not perceived credibility (or believability), of NEW Tx (as measured by the Credibility/ Expectancy Questionnaire) at baseline predicted treatment satisfaction (as measured by the Care Satisfaction Questionnaire) post-treatment. Manic symptoms at baseline predicted treatment satisfaction, and marital status predicted one’s expectations of lifestyle interventions. Data suggest that NEW Tx is a feasible and acceptable intervention for individuals with bipolar disorder and that further research is warranted to explore potential moderators of treatment expectations and credibility in this clinical population.